2018
DOI: 10.1123/kr.2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

The Embodied Origins of Infant Reaching: Implications for the Emergence of Eye-Hand Coordination

Abstract: This article reviews the literature on infant reaching, from past to present, to recount how our understanding of the emergence and development of this early goal-directed behavior has changed over the decades. We show that the still widely-accepted view, which considers the emergence and development of infant reaching as occurring primarily under the control of vision, is no longer sustainable. Increasing evidence suggests that the developmental origins of infant reaching is embodied. We discuss the implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…This is consistent with work from Corbetta et al. () revealing the importance of holding leading to rich visual input.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with work from Corbetta et al. () revealing the importance of holding leading to rich visual input.…”
Section: Discussionsupporting
confidence: 92%
“…Manual engagement with objects helps children discover the rich physical features of objects, including size, texture, and shape. Through exploration of these features, children learn to refine their actions and develop a sense of agency in dealing with their physical and social surroundings (Corbetta, Wiener, Thurman, & McMahon, ). Manual engagement also largely contributes to a child's first‐person view of objects (Smith et al., ), which predicts object name learning during social play (Pereira et al., ).…”
Section: Sustained Attention During Free Playmentioning
confidence: 99%
“…Importantly, their inability to produce successful grasps is not due to an immature motor system (Wallace & Whishaw, 2003), to low visual acuity (Banks & Salapatek, 1978) or to undeveloped stereovision (Braddick et al, 1980; Held, Birch, & Gwiazda, 1980), but rather to an unformed mapping between visual inputs and motor plans. This visuomotor mapping is thought to be achieved through an embodied process that requires infants to rely on proprioceptive and, more generally, haptic inputs from their reaching hand (Corbetta, Thurman, Wiener, Guan, & Williams, 2014; Corbetta, Wiener, Thurman, & McMahon, 2018; Thomas, Karl, & Whishaw, 2015). Our findings suggest that valuable haptic spatial cues provided by the hand holding the object could also assist the visuomotor learning process by promoting the development of precise visually controlled reach and grasp movements.…”
Section: Discussionmentioning
confidence: 99%
“…By 18–20 weeks all infants studied by Provine and Westerman (1979) made contralateral reaches. Studies have also shown that reaching to an object in external space becomes faster, more efficient, and more direct during the first year (Thelen et al, 1993; Berthier and Keen, 2006; Rönnqvist and Domellöf, 2006; D’Souza et al, 2017; Corbetta et al, 2018). Furthermore, reaching is not limited to stimuli that are perceived visually.…”
Section: Introductionmentioning
confidence: 99%